Study guides

☆☆

Q: 5x plus 3y equals 17

Write your answer...

Submit

Still have questions?

Related questions

Multiply the bottom equation by -1

5x+3y

(1, 4)

2x + 3y = 17 3x + 4y = 24 (2x + 3x) + (3y + 4y) = (17 + 24) 5x + 7y = 41

(2,7)

How do you add 2x plus 3y equals 18 in 5x-y equals 11

(9,2)

No.

5x+3y = -2 3y = -5x-2 y = -5/3x-2/3 Slope: -5/3

A system? Try elimination 3(8X - Y = 4) 5X + 3Y = 17 24X - 3Y = 12 5X + 3Y = 17 -------------------------+ 29X = 29 X = 1 -----------find Y 8(1) - Y = 4 - Y = - 4 Y = - 1 -----------check By inspection one can see this is inconsitent

(10,13)

If 5x plus 3y equals 13, the x equals 2 and y equals 1. This is because 5x2=10 and 3x1=3, and 10+3=13.

x = 8y = 6(5x8) + (3x6) = 58(5x8) - (3x6) = 22

The slope is -5/3.

Slope = - 5/3

Solve this system of equations. 5x+3y+z=-29 x-3y+2z=23 14x-2y+3z=-18 Write the solution as an ordered triple.

2x + 4y - 5x + 3y = 7y - 3x

the simplest form of 5x + 3y +2x - 6y is 7x-3y

That depends on what the value of x is.

13x - 9y - 10

5x+3 = -17 5x = -17-3 5x = -20 x = -4

5x + (3y-x) + (10-2y) = 5x + 3y - x + 10 -2y = 5x - x + 3y - 2y + 10 = 4x + y +10

1.67 or 1.667

5x -3y = -6 -3y = -5x -6 y = 5/3x+2 in slope intercept form

Convert the equation to the standard slope intercept form of y = mx + c, where the value of m is the slope. -5x + 3y = 3 3y = 5x + 3 y = 5/3x + 1 Then the slope is 5/3.